Perbandingan Kata Bahasa Indonesia dan Bahasa Arab (Tinjauan Struktur dan Semantik) (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
The history of the linguistic family reveals that a significant portion of the Arabic language has been in use since ancient times in daily life. The absorption of words from Arabic into Indonesian occurs significantly, with 2,336 Arabic vocabularies becoming an integral part of the Indonesian language. This process is triggered by the arrival of Middle Eastern traders in the 7th to 8th centuries AD and the spread of Islam in the 11th and 12th centuries AD in the Nusantara region (Hadi, 1995). The age of the Arabic language in Nusantara has surpassed 12 centuries, indicating an enduring influence over the centuries. Although Indonesian absorbs many words from Arabic, there are also homonyms, where similar words have different meanings (Chaer, 2003, p. 302). This research indicates that a profound understanding of the history of the Arabic language in Nusantara is crucial, not only to depict linguistic evolution but also to delineate the complexity of meanings and structural differences between the two languages.